Multifrequency time-harmonic elastography for the measurement of liver viscoelasticity in large tissue windows - Tzschaetzsch, Heiko; Ipek-Ugay, Selcan; Manh Nguyen Trong; Eggers, Jonathan; Gentz, Enno; Fischer, Thomas; Schultz, Michael; Braun, Juergen; Sack, Ingolf; Guo, Jing (Ultrasound in Medicine and Biology, 2015)
Elastography of the liver for the non-invasive diagnosis of hepatic fibrosis is an established method. However, investigations of obese patients or patients with ascites are often limited by small and superficial elastographic windows. Therefore, multifrequency time-harmonic elastography (THE) based on time-resolved A-line ultrasound has recently been developed for measuring liver viscoelasticity in wide soft tissue windows and at greater depths. In this study, THE was integrated into a clinical B-mode scanner connected to a dedicated actuator bed driven by superimposed vibrations of 30- to 60-Hz frequencies. The resulting shear waves in the liver were captured along multiple profiles 7 to 14 cm in width and automatically processed for reconstruction of mean efficient shear wave speed and shear wave dispersion slope. This new modality was tested in healthy volunteers and 22 patients with clinically proven cirrhosis. Patients could be separated from controls by higher shear wave speeds (3.11 ± 0.64 m/s, 2.14-4.81 m/s, vs. 1.74 ± 0.10 m/s, 1.60-1.91 m/s) without significant degradation of data by high body mass index or ascites. Furthermore, the wave speed dispersion slope was significantly (. p= 0.0025) lower in controls (5.2 ± 1.8 m/s/kHz) than in patients (39.1 ± 32.2 m/s/kHz). In conclusion, THE is useful for the diagnosis of cirrhosis in large tissue windows.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Ascites; Liver cirrhosis; Multifrequency vibrations; Obesity; Shear wave speed dispersion; Time-harmonic elastography